Short- and long-term effects of stress during adolescence on emotionality and HPA function of animals exposed to alcohol prenatally. (December 2016) - Raineki, Charlis; Chew, Leanne; Mok, Perry; Ellis, Linda; Weinberg, Joanne
Highlights: Adolescent CMS increased basal corticosterone and reduced weight gain in all groups. PAE induced depressive-like behavior in adolescent males. PAE and adolescent CMS induced anxiety-like behavior in adult females. PAE and adolescent CMS reduced CRHR1 in the basolateral amygdala in adult females. PAE reduced CRHR1 in the mPFC in adult males. Abstract: Prenatal alcohol exposure (PAE) is associated with extremely high rates of psychopathologies, which may be mediated by the hypothalamic-pituitary-adrenal (HPA) dysregulation observed in exposed individuals. Of relevance, PAE carries an increased risk of exposure to stressful environments throughout life. Importantly, stressful experiences during adolescence increase vulnerability to psychopathologies. However, little is known about how adolescent stressful experiences in the context of PAE-induced HPA dysregulation may further alter the developmental trajectory and potentially contribute to the disproportionally high rate of psychopathologies observed in this population. Here we investigate the short- and long-term effects of adolescent chronic mild stress (CMS) on the emergence of anxiety-/depressive-like behaviors (open-field and forced swim test – FST) and on HPA activity (corticosterone and type 1 CRH receptor – CRHR1) in PAE male and female rats. Under non-CMS conditions, open field results indicate that PAE induced inappropriate behavior (increased time in center) in males and females, with increased activity in female adolescents, but anxiety-like behavior in adult PAE females. Conversely, FST results indicate that PAE induced depressive-like behavior in adolescent males. Exposure to CMS resulted in increased activity in adolescent males and anxiety-like behaviors in adult females. Moreover, PAE and/or CMS altered corticosterone and CRHR1 expression in the mPFC and amygdala. Together, these results suggest that PAE and adolescent CMS induce dynamic neurobehavioral alterations that manifest differently depending on the age and sex of the animal. These results highlight the importance of using both sexes as well as an ontogenetic approach when investigating the effects of environmental adversity.